Adults with autism in the workplace and their work performance - Yap, Dona Maria Yapchiongco (2008)
This research aimed to determine the performance of working adults with autism in the workplace based on the quality of work, productivity, knowledge of the job, adaptability, dependability, initiative and resourcefulness, interpersonal relations, customer service, and attendance. This study used a combination of qualitative and quantitative research mainly interview schedule and research-adapted performance evaluation questionnaire. Results indicate that employment is acquired through social connections or specially-arranged employment. Tasks and duties are done routinely to provide a stress free work environment. Attendance attained the highest score without assistance and without prompt while productivity received the lowest with assistance and verbal prompting. The overall work performance obtained a satisfactory evaluation.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Autistic people -- Employment -- Philippines; Autistic people -- Rating of -- Philippines; People with disabilities -- Employment -- Philippines